Downward Real Wage Rigidity and Equal Treatment Wage Contracts: Evidence from Germany - Heiko Stüber; Andy Snell (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Theoretical models of downward real wage rigidity generate asymmetric wage cyclicality with real wages being rigid in "bad" times but upwardly flexible during "good". In this paper we use an administrative panel dataset from Germany to establish that such asymmetries are very salient in Germany. We find that the semi elasticity of real wages with respect to unemployment is very close to zero when unemployment is above its long term average but large and highly significant when below. We also find that equal treatment - where new hires are exposed to the same cyclicality as incumbents - is supported in our data. Equal treatment is a central driver of downwardly rigid wages in many contracting models (e.g., Hall, 2005; Gertler and Trigari, 2009; Snell and Thomas, 2010). We find that an equal treatment model in which wages are smoothed by firms can generate the asymmetric wage cyclicality found in the panel data. The model also can match most of the properties of wages and unemployment. It cannot however match the persistence of the German unemployment rate. We conjecture that extending the model to allow for search frictions and/or adjustment costs may rectify this deficiency.
Keywords: E24; E32; C23; 330